2020
DOI: 10.3389/fgene.2020.570530
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Signatures of Prognosis Prediction for Melanoma Using a Hypoxia Score

Abstract: Melanoma is one of the most aggressive cancers. Hypoxic microenvironment affects multiple cellular pathways and contributes to tumor progression. The purpose of the research was to investigate the association between hypoxia and melanoma, and identify the prognostic value of hypoxia-related genes. Based on the GSVA algorithm, gene expression profile collected from The Cancer Genome Atlas (TCGA) was used for calculating the hypoxia score. The Kaplan–Meier plot suggested that a high hypoxia score was correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 72 publications
2
24
0
Order By: Relevance
“… 125 GSDMC is hypomethylated in lung adenocarcinoma (LUAD) cells, and its upregulation implies poor prognosis in LUAD patients. 155 Also, GSDMC is linked to metastasis in malignant melanoma, 123 , 164 and the high expression of GSDMC is related to the poor survival of breast cancer. Upon hypoxia, the GSDMC gene is transcriptionally activated for nPD‐L1/p‐Y705‐signal transducer and activator of transcription 3 (STAT3) complex binding to the STAT3‐binding site in the promoter region of GSDMC .…”
Section: The Mechanism Of the Pyroptosis Pathwaymentioning
confidence: 99%
“… 125 GSDMC is hypomethylated in lung adenocarcinoma (LUAD) cells, and its upregulation implies poor prognosis in LUAD patients. 155 Also, GSDMC is linked to metastasis in malignant melanoma, 123 , 164 and the high expression of GSDMC is related to the poor survival of breast cancer. Upon hypoxia, the GSDMC gene is transcriptionally activated for nPD‐L1/p‐Y705‐signal transducer and activator of transcription 3 (STAT3) complex binding to the STAT3‐binding site in the promoter region of GSDMC .…”
Section: The Mechanism Of the Pyroptosis Pathwaymentioning
confidence: 99%
“…Meanwhile, the differential expression analysis and univariate Cox analysis were firstly constructed to screen these genes, which might also help to discover more specific prognostic markers to screen for innovative treatment targets. Like signatures associated with immune checkpoint (Tian et al, 2020), lncRNAs (Liu et al, 2019), ferroptosis (Luo & Ma, 2021), and hypoxia (Shou et al, 2020), our risk signature also had high predictive accuracy for the OS of patients with CM. We also analyzed whether immune status, tumor microenvironment, immune components, tumor stemness, and chemotherapeutic drug sensitivity corresponded to the gene signature and pyroptosis genes, and found that our risk signature conferred advantages compared with those described above.…”
Section: Discussionmentioning
confidence: 76%
“…We also compared the our model to other researchers such as Shou et al constructed a model based on hypoxic genes, but it did not work well in the validation set and there was no complete 1, 3 and 5 year predictive capability. 28 Wu et al constructed a prediction model for SKCM, but the sample size of the validation set was too small to represent the accuracy of the model. 29 Two genes (ALOX5, CHAC1) collaborated to create a prognosis model that accurately estimated the prognosis of patients with SKCM, according to our findings.…”
Section: Discussionmentioning
confidence: 99%